Hip arthroplasty - study correlating intra operative stable range of motion with postoperative functional activity - Singhi, Tushar; Kapoor, Udit; Rao, Ashith (International Journal of Research in Orthopaedics, 2020)
Background: Squatting and sitting cross-legged is a part of lifestyle both for employment and for daily ablutions. When these activities can be allowed after hip arthroplasty is not documented. The aim of this study is to identify if patients having good intra-operative stability with the posterior approach, can start high flexion activities early. Methods: In this retrospective study, all hip arthroplasty patients done from 2013-2017 were considered for inclusion. Patients were evaluated for intra-operative stable range of motion and patients who were stable were encouraged to do cross-legged sitting from 2 weeks after surgery and squatting from 6 weeks after surgery. The follow-up visits were at 6-weeks, 3-months and 1-year after surgery. Parameters assessed were Harris hip score, short form survey-12 (SF-12) score, limb length discrepancy, range of motion and ability to sit cross-legged and squat. All the patients were again called for a follow-up visit and the parameters were reassessed. Results: Sixty patients were included in the study. Mean follow-up was 2 years 3 months. Mean Harris hip score and SF-12 showed improvement from 64.8 and 19.5 at 3 months to 88.3 and 37.8 respectively at last follow-up. At the end of 3 months, 85% patients could sit cross-legged and 50% could squat. At one year, the corresponding figures were 85% and 70%. Conclusions: If intra-operative range of motion testing is satisfactory, early initiation of high flexion hip activities is safe.